Advancements in Diabetes Mellitus: Pathogenesis, Current Therapies, and Emerging Treatment Strategies - Narayan, Jay; Dixit , Anjali; Sharma, Ram Babu; Tomer, Sakshi (Journal of Drug Delivery and Therapeutics, 2025)
The incidence of diabetes mellitus is sharply increasing globally, making it a serious public health concern. More than 463 million people were impacted in 2019, and estimates indicate that by 2045, that figure may rise to 700 million. Diabetes causes serious consequences, such as retinopathy, nephropathy, and cardiovascular illnesses. It is characterised by persistent hyperglycemia brought on by either inadequate insulin secretion, impaired insulin action, or both. Type 1 diabetes mellitus (T1DM) and Type 2 diabetes mellitus (T2DM), both with unique aetiologies and treatment needs, are part of the complicated pathophysiology of diabetes. In contrast, T2DM is primarily associated with insulin resistance and is influenced by both genetic and environmental factors, T1DM, which is often autoimmune in nature, results in total insulin insufficiency. Insulin therapy, oral hypoglycemic medications, and lifestyle changes are examples of traditional management techniques; however, they frequently fall short of providing the best possible glycaemic control. Recent developments in diabetes treatment have led to novel therapeutic approaches, including immunological therapies, novel pharmacological agents, and nanotechnology-based drug delivery systems. The goals of these new therapies are to reduce the risk of complications, enhance patient compliance, and improve glycemic management. This overview provides an overview of the development of diabetes treatments, the pathophysiology of the condition, available treatment options, and the promise of new drugs and methods for managing the condition. We can gain a better understanding of the future of diabetes care and the significance of creating individualised treatment plans to improve patient outcomes and quality of life by investigating these developments. Keywords: Diabetes Mellitus; Hyperglycemia; Type 1 Diabetes (T1DM); Type 2 Diabetes (T2DM); Novel Therapeutic Strategies